Penetrating Rectal Wound in Domestic Injury - AS, Nur Hayati (IIUM Medical Journal Malaysia, 2019)
An 11-year-old boy tried to jump over a metal rod but landed on it presented with perianal pain and rectal bleeding. On examination, there is a 1.5cm perineal laceration. His blood results showed a normal TWC with a normal abdominal and chest radiographs. His vital signs were within normal limits. He was planned for bedside T&S by ED team but deferred as persistent blood oozing from rectal, thus referred to Paediatric Surgery. Upon review, there was 2x1cm perianal laceration at 7 o’clock, abrasion wound at 10 & 12 o’clock. Ultrasound showed no free fluid. He was taken to emergency OT for EUA, intraoperative findings were a perianal laceration, on table sigmoidoscopy showed posterior rectal wall irregularities with slow oozing blood from it, however, no obvious perforation seen. The patient developed fever with lower abdominal tenderness on the following day. Urgent CECT abdomen pelvis performed and showed features of extraperitoneal rectal perforation. He was treated conservatively with antibiotics and NBM with parenteral nutrition support. He made a good recovery and was discharged home on day 9. Pediatric perineal impalement injuries often caused by falls on an offending object. These children are prone to severe injuries as compared to adults and the lesions in the pediatric perineum may appear innocuous, but can be potentially life-threatening and surgically challenging. Perineal impalement injuries in children are classified as transanal or perineal and further subdivided as extraperitoneal or intraperitoneal. This classification method is used to predict potential injuries and develop treatment guidelines. Evaluation of perineal impalement injuries in children needs to be thorough even in the presence of minimal or no symptoms.